a)
To find the difference quotient we will do
![(f(x+h)-f(x))/(h)](https://img.qammunity.org/2023/formulas/mathematics/high-school/17t90244gmpmpb277486zmwgro40kqpbqz.png)
But f(x) = 4x, therefore f(x+h) = 4(x+h). Then
![(f(x+h)-f(x))/(h)=(4(x+h)-4x)/(h)](https://img.qammunity.org/2023/formulas/mathematics/college/ph5esb2nh7bgduf4ze6t7u9pkrq37joa5v.png)
Now we just simplify the expression
![(4(x+h)-4x)/(h)=(4x+4h-4x)/(h)=(4h)/(h)=4](https://img.qammunity.org/2023/formulas/mathematics/college/4ef9euvsbrqxdq48gognn71iv1dsi7smgc.png)
Therefore
![(f(x+h)-f(x))/(h)=4](https://img.qammunity.org/2023/formulas/mathematics/college/rxancqxdbqorlk8x8nqvdzs1895iqrff2h.png)
As expected, because the function f is a linear function, then it must be a constant.
b)
As we can see we don't have the term "h" in the difference quotient, then we can easily solve the limit by just repeating the result:
![\lim _(h\rightarrow0)(f(x+h)-f(x))/(h)=\lim _(h\rightarrow0)4=4](https://img.qammunity.org/2023/formulas/mathematics/college/gs5rghgvl6qgj5q9zbqnfetiaqvoj657q4.png)
Therefore
![f^(\prime)(x)=4](https://img.qammunity.org/2023/formulas/mathematics/college/qmv5oktelaw913z6n1eek28z10ldkhvj8z.png)
See that it's a constant function, it means that the slope will always be the same, doesn't matter the value of x.